Optimization of hydrolysis conditions for the production of shrimp hydrolysate by using protamex: effect of enzyme substrate (ES) ratio and time / Nurul Nadiah Ahmad Latif. - Ahmad Latif, Nurul Nadiah (2009)
The optimization of hydrolysis conditions which are enzyme substrate ratio ..and hydrolysis time for the production of shrimp hydrolysate by using protamex were studied. This study was done to obtain the optimum percentage for nitrogen recovery and degree of hydrolysis on the hydrolysis conditions. Methods for production of shrimp hydrolysate include homogenization, adjustment of pH and temperature, addition of enzyme and hydrolysis time which are based on response surface methodology (RSM) suggestion, termination of hydrolysis, cooled and centrifuged the hydrolysis sample, collection of supernatant and analysis for percentage of nitrogen recovery and degree of hydrolysis. Total nitrogen in supernatant was determined by using Kjeldhal method. The percentage of degree of hydrolysis was determined by using modified formol titration method. The data that were obtained from the experiment were accomplished by employing the RSM using Design Expert 4 Software. By fitting the experimental data to the equation, the percentage nitrogen recovery (%NR) optimum levels for time (240 min), ES ratio (0%), (%NR) (3.90308) with desirability (0.657) at constant pH 6 and constant temperature 60°C were determined. For percentage degree of hydrolysis (%DH), the optimum levels for time (0 min), ES ratio (4%), %DH (2.80186) with desirability (0.693) were determined.